Peran Kecerdasan Sosial terhadap Resiliensi pada Mahasiswa Tingkat Awal - Annisa Andriani; Ratih Arruum Listiyandini (Psympathic : Jurnal Ilmiah Psikologi, 2017)
First-year university students experienced various demands and problems, such as developmental tasks, role transition processes, academic’s demands, and anxieties. To be more resilient when facing those demands and problems, increasing quality and quantity of social connection are needed; therefore, they need social intelligence. This research examined the role of social intelligence on resilience. 177 college freshmen in Jakarta were chosen with incidental sampling technique. This study used adaptation of Tromso Social Intelligence Scale to measure social intelligence and adaptation of Connor Davidson – Resilience Indicator Scale to measure resilience. Simple regression analysis shows that social intelligence contributes in about 16% on resilience. Multiple regression analysis shows that  Social Information Processing has the most significant role among other dimensions of social intelligence. This dimension describes the ability to understanding various (social) messages in social environment. Thus, social intelligence development is imperative for enhancing the resilience of first year students in the university.